2015
DOI: 10.3390/toxins7062071
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol Impairs Weight Gain and Affects Markers of Gut Health after Low-Dose, Short-Term Exposure of Growing Pigs

Abstract: Deoxynivalenol (DON) is one of the major mycotoxins produced by Fusarium fungi, and exposure to this mycotoxin requires an assessment of the potential adverse effects, even at low toxin levels. The aim of this study was to investigate the effects of a short-term, low-dose DON exposure on various gut health parameters in pigs. Piglets received a commercial feed or the same feed contaminated with DON (0.9 mg/kg feed) for 10 days, and two hours after a DON bolus (0.28 mg/kg BW), weight gain was determined and sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 72 publications
12
59
2
Order By: Relevance
“…Deng (Deng et al, 2015) investigated the distribution of DON in plasma, bile and 27 tissues after i.v. The same conclusions were reached by Alizadeh (Alizadeh et al, 2015), who measured the effects of a short-term and comparable DON exposure (0.28 mg/kg bw) on various gut health parameters in pigs. The same conclusions were reached by Alizadeh (Alizadeh et al, 2015), who measured the effects of a short-term and comparable DON exposure (0.28 mg/kg bw) on various gut health parameters in pigs.…”
Section: Ochratoxin Asupporting
confidence: 71%
“…Deng (Deng et al, 2015) investigated the distribution of DON in plasma, bile and 27 tissues after i.v. The same conclusions were reached by Alizadeh (Alizadeh et al, 2015), who measured the effects of a short-term and comparable DON exposure (0.28 mg/kg bw) on various gut health parameters in pigs. The same conclusions were reached by Alizadeh (Alizadeh et al, 2015), who measured the effects of a short-term and comparable DON exposure (0.28 mg/kg bw) on various gut health parameters in pigs.…”
Section: Ochratoxin Asupporting
confidence: 71%
“…We also observe the interference of DON with genes involved in other biological functions such as oxidative stress, cell cycle molecular transport and mitochondrial functions. As recently described in vivo (Alizadeh et al 2015), a decreased expression of mRNA levels of efflux transporters was also observed in intestinal explants exposed to DON. Studies reported that DON is a substrate for ABC transporter (Videmann et al 2007); thus, a decrease expression of efflux protein would decrease uptake of DON by intestinal cells and therefore decrease its toxicity.…”
Section: Figsupporting
confidence: 52%
“…Especially, IL-22 in the gut is able to stimulate intestinal epithelial cells to produce antimicrobial peptides, enhance the intestinal epithelial barrier of mucus and promote intestinal repair (Hou et al, 2018;Parks et al, 2015). Pathogens such as enterotoxigenic Escherichia coli (ETEC) and mycotoxin in contaminated feed are destructive to intestinal epithelial cells, which cause enteritis and seriously threatens gut health of pigs (Alizadeh et al, 2015;Lee et al, 2016;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%